2000
DOI: 10.1093/genetics/155.3.1231
|View full text |Cite
|
Sign up to set email alerts
|

Ariadne-1: A Vital Drosophila Gene Is Required in Development and Defines a New Conserved Family of RING-Finger Proteins

Abstract: We report the identification and functional characterization of ariadne-1 (ari-1), a novel and vital Drosophila gene required for the correct differentiation of most cell types in the adult organism. Also, we identify a sequence-related gene, ari-2, and the corresponding mouse and human homologues of both genes. All these sequences define a new protein family by the Acid-rich, RING finger, B-box, RING finger, coiled-coil (ARBRCC) motif string. In Drosophila, ari-1 is expressed throughout development in all tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(13 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…The ARI gene family has been identified in human [ 21 , 22 , 23 ], Drosophila [ 24 ], mouse [ 25 ], and Arabidopsis [ 9 ]. However, the mechanism and functions of ARI proteins are largely unknown, for only limited literature is available regarding the functional importance of these genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ARI gene family has been identified in human [ 21 , 22 , 23 ], Drosophila [ 24 ], mouse [ 25 ], and Arabidopsis [ 9 ]. However, the mechanism and functions of ARI proteins are largely unknown, for only limited literature is available regarding the functional importance of these genes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanism and functions of ARI proteins are largely unknown, for only limited literature is available regarding the functional importance of these genes. Some ARI proteins are involved in E2 enzyme interactions in Drosophila [ 24 ] and human [ 23 ]. Ubiquitination activity is only proven in ARI8 in A. thaliana [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The newly discovered RING-IBR-RING (RBR) E3 ligases are proved as a unique family of RING-HECT hybrid E3 ligases, which are not the same as RING and HECT types. The RBR E3 ligases are specialized by a conserved catalytic region, including a RING1, a central in-between-RINGs (IBR) and a RING2 domain [ 62 ]. RING1 can recruit the E2 loaded with ubiquitin, and RING2 domain contains a catalytic cysteine.…”
Section: The Classification and Features Of E3 Ligasesmentioning
confidence: 99%
“…A previous study demonstrated that an E3 ligase, ARIH2, which is derived from the really interesting new gene (RING) in between RING (RBR) E3 ligase family, suppresses NLRP3 inflammasome activation [77]. ARIH2 can interact with the NACHT domain (aa220-575) of NLRP3 through its RING 2 domain to induce K48-and K63-linked polyubiquitination.…”
Section: Arih2 (Ariadne Homolog 2)mentioning
confidence: 99%